A Review of Carbon-Based Materials for Safe Lithium Metal Anodes - Liu, Yan (Front Chem, 2019)
Lithium metal is a promising anode material with extremely high theoretical specific capacity (3,860 mA h g(−1)), low density (0.59 g cm(−3)), and the lowest negative electrochemical potential of all potential candidates (−3.04 V vs. the standard hydrogen electrode). However, uncontrollable Li dendrite growth leads to a short lifespan and catastrophic safety hazards, which has restricted its practical application for many years. Some effective strategies have been adopted regarding these challenges, including electrolyte modification, introducing a protective layer, nanostructured anodes, and membrane modification. Carbon-based materials have been demonstrated to significantly address the challenge of Li dendrites. In this review, carbon-based materials and their application and challenges in lithium metal anode protection have been discussed in detail. In addition, the applications of lithium anodes protected by carbon-based materials in Li-S batteries and Li-O(2) batteries have been summarized.